Răspuns :
a) -3x + 5 = -28
-3x + 5 + 28 = -28 + 28
3(-x + 11) = 0
x = 11
S = {11}
b) |x-3| = 13
x = 16 sau x = -10
S = {16,-10}.
-3x + 5 + 28 = -28 + 28
3(-x + 11) = 0
x = 11
S = {11}
b) |x-3| = 13
x = 16 sau x = -10
S = {16,-10}.
a) -3x+5= -28
- 3x = - 28 - 5
- 3x = - 33
x= - 33/ - 3
x=11
b) | x-3 | =13
1. x - 3 = 13 ⇒ x = 13 + 3 ⇒ x=16
sau
2. x - 3 = - 13 ⇒ x= - 13+3 ⇒ x= -10
S{ -10; 16}
- 3x = - 28 - 5
- 3x = - 33
x= - 33/ - 3
x=11
b) | x-3 | =13
1. x - 3 = 13 ⇒ x = 13 + 3 ⇒ x=16
sau
2. x - 3 = - 13 ⇒ x= - 13+3 ⇒ x= -10
S{ -10; 16}